No Small Matter : The Impact of Poverty, Shocks, and Human Capital Investments in Early Childhood Development - Alderman, Harold (World Bank, 2012)
The relative lack of attention to early childhood development in many developing countries remains a puzzle, and an opportunity. There is increasing evidence that investments in the nutritional, cognitive, and socio-emotional development of young children have high payoffs. Researchers and development practitioners are building on this evidence to raise the topic's profile and bring it to the attention of decision makers. This volume is an important contribution to these efforts. It thoroughly and carefully reviews the most recent empirical literature linking early childhood development outcomes, poverty, and shocks. In doing so, it brings an added perspective to the debate and makes the case that investments in the first years of life have the potential to be a critical component of poverty reduction strategies. The volume also goes beyond simply documenting the consequences of insufficient or inadequate focus on early childhood and identifies the range of policy options available to policy makers. The Human Development Perspectives series seeks to present thorough research findings on issues of critical strategic importance for developing countries. At its core is the perspective that investments in human capital are an essential aspect of efforts to promote global development and eradicate poverty. This volume makes it convincingly clear that investing in and protecting the human capital of young children is no small matter.